Ocular pharmacology of topotecan and its activity in retinoblastoma - Schaiquevich, Paula Susana (2014)
Purpose: To review the ocular pharmacology and antitumor activity of topotecan for the treatment of retinoblastoma by an evaluation of different routes of administration. Methods: Systematic review of studies available at PubMed using the keywords retinoblastoma, topotecan, and camptothecins, including preclinical data such as cell lines and animal models, as well as clinical studies in patients with retinoblastoma. Results: Forty-two available studies were reviewed. Evidence of antitumor activity against retinoblastoma as a single agent is based on data on cell lines and a limited number of affected patients with intraocular and extraocular disease when given in a protracted schedule. Evidence of additive or synergistic activity in combination with other agents such as carboplatin, melphalan, and vincristine was reported in preclinical and clinical models. In animal models, pharmacokinetic evaluation of topotecan administered by the periocular route shows that most of the drug reaches the vitreous through the systemic circulation. Topotecan administered by intravitreal injection shows high and sustained vitreal concentrations with limited systemic exposure and lack of retinal toxicity at a dose of up to 5 μg. Topotecan administered intraophthalmic artery shows higher passage to the vitreous compared with periocular administration in a swine model. Conclusion: Topotecan alone or in combination is active against retinoblastoma. It shows a favorable passage to the vitreous when given intravenously and intraarterially, and ocular toxicity is minimal by all routes of administration. However, its clinical role, optimal dose, and route of administration for the treatment of retinoblastoma are to be determined.